Highly Strained Heterometallacycles of Group 4 Metallocenes with Bis(diphenylphosphino)methanide Ligands. Issue 23 (8th April 2013) - Haehnel, Martin; Hansen, Sven; Priebe, Jacqueline B.; Spannenberg, Anke; Arndt, Perdita; Brückner, Angelika; Rosenthal, Uwe
Abstract A study of the coordination chemistry of different bis(diphenylphosphino)methanide ligands [Ph2PC(X)PPh2] (X=H, SiMe3) with Group 4 metallocenes is presented. The paramagnetic complexes [Cp2Ti{κ2‐P, P‐Ph2PC(X)PPh2}] (X=H (3 a), X=SiMe3 (3 b)) have been prepared by the reactions of [(Cp2TiCl)2] with [Li{C(X)PPh2}2(thf)3]. Complex 3 b could also be synthesized by reaction of the known titanocene alkyne complex [Cp2Ti(η2‐Me3SiC2SiMe3)] with Ph2PC(H)(SiMe3)PPh2 (2 b). The heterometallacyclic complex [Cp2Zr(H){κ2‐P, P‐Ph2PC(H)PPh2}] (4 aH) has been prepared by reaction of the Schwartz reagent with [Li{C(H)PPh2}2(thf)3]. Reactions of [Cp2HfCl2] with [Li{C(X)PPh2}2(thf)3] gave the highly strained corresponding metallacycles [Cp2M(Cl){κ2‐P, P‐Ph2PC(X)PPh2}] (5 aCl and 5 bCl) in very good yields. Complexes 3 a, 4 aH, and 5 aCl have been characterized by X‐ray crystallography. Complex 3 a has also been characterized by EPR spectroscopy. The structure and bonding of the complexes has been investigated by DFT analysis. Reactions of complexes 4 aH, 5 aCl, and 5 bCl did not give the corresponding more unsaturated heterometallacyclobuta‐2, 3‐dienes.